2013
DOI: 10.1111/j.1477-2574.2012.00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the placement of a cystic duct tube after a hepatic resection help reduce the incidence of post‐operative bile leak?

Abstract: The usefulness of the C tube in preventing post-hepatectomy bile leak could not be confirmed; however, both bile leak requiring clinical management and long hospitalization after a major hepatectomy could be reduced with C tube use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…We know that complete drainage of intra-abdominal fluid collections by operative drains, secondary drainage puncture, and endoscopic nasobiliary drainage can help with this goal, but we also showed that there was a marginal tendency toward decreased organ/space SSI rates among patients with cystic duct tubes that were placed preemptively for bile leakage. This is consistent with a previous report showing that a transcystic drainage tube inserted after hepatectomy could help prevent or treat bile leakage [26]. Because cystic tubes were inserted in patients having a high risk of postoperative bile leakage, although it did not reach statistical difference, the result that the rate of organ/space SSI in patients with cystic tubes was lower than that in those without cystic tubes may have some clinical value; that is, the cystic tube might have prevented subsequent organ/space SSI after bile leakage.…”
Section: Discussionsupporting
confidence: 81%
“…We know that complete drainage of intra-abdominal fluid collections by operative drains, secondary drainage puncture, and endoscopic nasobiliary drainage can help with this goal, but we also showed that there was a marginal tendency toward decreased organ/space SSI rates among patients with cystic duct tubes that were placed preemptively for bile leakage. This is consistent with a previous report showing that a transcystic drainage tube inserted after hepatectomy could help prevent or treat bile leakage [26]. Because cystic tubes were inserted in patients having a high risk of postoperative bile leakage, although it did not reach statistical difference, the result that the rate of organ/space SSI in patients with cystic tubes was lower than that in those without cystic tubes may have some clinical value; that is, the cystic tube might have prevented subsequent organ/space SSI after bile leakage.…”
Section: Discussionsupporting
confidence: 81%
“…A beneficial impact of T‐tube insertion in the choledochal duct on postoperative biliary fistula has also been reported in a subgroup of patients undergoing extended hemihepatectomy. In contrast, other authors have found no evidence of a difference in frequency of bile leakage in patients with or without transcystic tube insertion. Some studies, including experimental animal studies, have even indicated that external biliary drainage is not only ineffective but is in fact associated with worse liver regeneration after hepatectomy owing to loss of bile acid from the intestine during external drainage.…”
Section: Discussionmentioning
confidence: 90%
“…According to the literature, a biliary fistula rate of 15 per cent could be expected in the control group. The sample size was estimated to reveal a difference of 10 per cent between the two groups for the primary endpoint, which would be clinically relevant.…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations